Superstar CEOS - Malmendier, Ulrike 1973-; Tate, Geoffrey (NBER working paper, 2008)
"Compensation, status, and press coverage of managers in the U.S. follow a highly skewed distribution: a small number of 'superstars' enjoy the bulk of the rewards. We evaluate the impact of CEOs achieving superstar status on the performance of their firms, using prestigious business awards to measure shocks to CEO status. We find that award-winning CEOs subsequently underperform, both relative to their prior performance and relative to a matched sample of non-winning CEOs. At the same time, they extract more compensation following the award, both in absolute amounts and relative to other top executives in their firms. They also spend more time on public and private activities outside their companies, such as assuming board seats or writing books. The incidence of earnings management increases after winning awards. The effects are strongest in firms with weak governance, even though the frequency of obtaining superstar status is independent of corporate governance. Our results suggest that the ex-post consequences of media-induced superstar status for shareholders are negative"--National Bureau of Economic Research web site